Violence in Divorce and Judicial Authority: An Indonesia–Malaysia Study - Susantin, Jamiliya; Mufidah Ch; Inah (Al-Manhaj: Journal of Indonesian Islamic Family Law, 2025)
This research examines how Indonesia and Malaysia handle economic domestic violence as grounds for divorce. Both countries face fragmented court jurisdictions—in Indonesia, divorce cases go to Religious Courts while criminal domestic violence cases go to District Courts; in Malaysia, Islamic divorces go to Syariah Courts while victim protection falls under Civil Courts. This fragmentation creates legal uncertainty, lengthy processes, high costs, and barriers to justice for victims, especially economically dependent women. The study recommends an integrated justice system with one-stop services, simplified evidence procedures, fee waivers, a three-month maximum resolution period, and e-Court technology to harmonize legal certainty, justice, and efficiency.